Pembrolizumab versus placebo as adjuvant therapy in resected stage IIB or IIC melanoma (KEYNOTE-716): distant metastasis-free survival results of a multicentre, double-blind, randomised, phase 3 trial. Issue 11 (November 2022) - Long, Georgina V; Luke, Jason J; Khattak, Muhammad A; de la Cruz Merino, Luis; Del Vecchio, Michele; Rutkowski, Piotr; Spagnolo, Francesco; Mackiewicz, Jacek; Chiarion-Sileni, Vanna; Kirkwood, John M; Robert, Caroline; Grob, Jean-Jacques; et al.
Summary: Background: Patients with stage IIB or IIC melanoma who undergo surgery alone are at a substantial risk for disease recurrence. Adjuvant pembrolizumab significantly improved recurrence-free survival versus placebo in stage IIB or IIC melanoma in the first interim analysis of the KEYNOTE-716 trial. Here, we report results from the secondary endpoint of distant metastasis-free survival (prespecified third interim analysis), and recurrence-free survival with longer follow-up. Methods: KEYNOTE-716 is a multicentre, double-blind, placebo-controlled, crossover or rechallenge, randomised, phase 3 trial done at 160 academic medical centres and hospitals across 16 countries. Eligible patients were aged 12 years and older with newly-diagnosed, completely resected, and histologically confirmed stage IIB (T3b or T4a) or IIC (T4b) cutaneous melanoma; negative sentinel lymph node biopsy; and an Eastern Cooperative Oncology Group performance status of 0–1. Patients were randomly assigned (1:1) to receive either 200 mg of pembrolizumab (2 mg/kg up to a maximum of 200 mg in paediatric patients) or placebo, both intravenously, every 3 weeks for 17 cycles (part 1) or until disease recurrence or unacceptable toxicity. Eligible patients with disease recurrence could receive further treatment with pembrolizumab in the part 2 crossover or rechallenge phase. Randomisation was done using an interactive response technology system and stratified by T category and paediatric status. The primary endpoint was investigator-assessed recurrence-free survival (assessed here with longer follow-up), and we report the prespecified third interim analysis of distant metastasis-free survival (secondary endpoint). Efficacy analyses were done in the intention-to-treat population (all patients who were randomly assigned, according to assigned group) and safety was assessed in all patients who were randomly assigned and received at least one dose of trial treatment, according to the treatment received. KEYNOTE-716 is registered at ClinicalTrials.gov, NCT03553836, and has completed recruitment. Findings: Between Sept 23, 2018, and Nov 4, 2020, 976 patients were randomly assigned to receive pembrolizumab (n=487) or placebo (n=489). At a median follow-up of 27·4 months (IQR 23·1–31·7), median distant metastasis-free survival was not reached (95% CI not reached [NR]–NR) in either group. Pembrolizumab significantly improved distant metastasis-free survival (hazard ratio [HR] 0·64, 95% CI 0·47–0·88, p=0·0029) versus placebo. Median recurrence-free survival was 37·2 months (95% CI NR–NR) in the pembrolizumab group and not reached in the placebo group (95% CI NR–NR). The risk of recurrence remained lower with pembrolizumab versus placebo (HR 0·64, 95% CI 0·50–0·84). The most common grade 3 or worse adverse events were hypertension (16 [3%] of 483 patients in the pembrolizumab group vs 17 [4%] of 486 patients in the placebo group), diarrhoea (eight [2%] vs one [<1%]), rash (seven [1%] vs two [<1%]), autoimmune hepatitis (seven [1%] vs two [<1%]), and increased lipase (six [1%] vs eight [2%]). Treatment-related serious adverse events occurred in 49 (10%) patients in the pembrolizumab group and 11 (2%) patients in the placebo group. No treatment-related deaths were reported. Interpretation: Adjuvant pembrolizumab is an efficacious treatment option for resected stage IIB and IIC melanoma, with significant improvement in distant-metastasis free survival versus placebo and continued reduction in the risk of recurrence with an adverse event profile consistent with previous studies of pembrolizumab. The overall benefit–risk of pembrolizumab continues to be positive in the adjuvant setting. Funding: Merck Sharp & Dohme, a subsidiary of Merck & Co.